Competition and Demographics - Amin, Mohammad (World Bank, Washington, DC, 2012)
Mainstream economics views demographic changes in the structure of households as of little relevance for the behavior of firms or the functioning of markets. The present paper dispels this view by arguing that changes in the number of non-workers could affect the intensity with which consumers search for best prices and therefore the level of competition. The author also analyzes the relationship between income and competition, which some studies suggest is negative. The author argues that the negative relationship is most likely due to the demographic factors discussed.